62=-3a+2

Simple and best practice solution for 62=-3a+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 62=-3a+2 equation:



62=-3a+2
We move all terms to the left:
62-(-3a+2)=0
We get rid of parentheses
3a-2+62=0
We add all the numbers together, and all the variables
3a+60=0
We move all terms containing a to the left, all other terms to the right
3a=-60
a=-60/3
a=-20

See similar equations:

| 6x+7=4x-6 | | 2(x+3)-3x=5-2x+1 | | -3-14x=319 | | 12x-12-11x=2 | | −4=z+3 | | 4.4x=-30.8 | | k=−4 | | x+1/2-x/4=5/2 | | m/14-9=-10 | | 10p^2-3=-12p | | x−2.8=1.6 | | 4x+5=23-3x+3 | | 42(4/7x=1/6) | | 33x=94x | | 2=9+n/3 | | 36-18n=50n+70 | | -5=-10x+25 | | 8x+4=−4+6x+18 | | -25+4(2x+5)=-51 | | -0.16x+0.02x=0.1x+0.4 | | 3x+6=-2x-6 | | 9x-x+3=19 | | 45y=450 | | 12m+12=32 | | 7x(7x-12=-72 | | 3w=68 | | (6x+5)4x=(4x×45)4x | | Y-10=4o | | 2(x+2)^2=2x(x+2) | | 2(x+2)^2=0 | | -7c=-3(4) | | X+9x-8=134 |

Equations solver categories